Engineering the Coherent Phonon Transport in Polar Ferromagnetic Oxide Superlattices - In Hyeok Choi; Seung Gyo Jeong; Do‐Gyeom Jeong; Ambrose Seo; Woo Seok Choi; Jong Seok Lee (Advanced Science)
Abstract Artificial superlattices composed of perovskite oxides serves as an essential platform for engineering coherent phonon transport by redefining the lattice periodicity, which strongly influences the lattice‐coupled phase transitions in charge and spin degrees of freedom. However, previous methods of manipulating phonons have been limited to controlling the periodicity of superlattice, rather than utilizing complex mutual interactions that are prominent in transition metal oxides. In this study on oxide superlattices composed of ferromagnetic metallic SrRuO3 and quantum paraelectric SrTiO3, phonon modulation by controlling the geometry of superlattice in atomic‐scale precision is realized, demonstrating the coherent phonon engineering using structural and magnetic phase transitions. By modulating the interface density, coherent‐incoherent crossover of the phonon transport at room temperature is observed, which is coupled with a change in interfacial structural continuity. Upon cooling, the close relation between phonon transport and multiple phase transitions is identified. In particular, the enhancement of the polar state in SrTiO3 layer at ≈200 K leads to the weakening of phonon coherence and a further reduction of thermal conductivity in superlattices compared to the bulk limit. These findings provide a guide to developing future thermoelectric nanodevices by engineering the coherence of phonons via the design of complex oxide heterostructures.